2004
DOI: 10.1128/aac.48.3.940-945.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, Pharmacokinetics, and Serum Bactericidal Activity of Intravenous Dalbavancin in Healthy Volunteers

Abstract: Fifty-two healthy adult male and female volunteers were enrolled in this double-blind study to determine the maximum tolerated dose, characterize the pharmacokinetics, and obtain serum bactericidal activity (SBA) data for intravenous dalbavancin. Subjects were assigned to single-or multiple-dose groups and randomized to receive dalbavancin or placebo intravenously over 30 min. Doses started at 140 mg in the single-dose group and with a 300-mg loading dose (LD), followed by six daily 30-mg maintenance doses (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
172
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 11 publications
5
172
0
3
Order By: Relevance
“…Investigators have demonstrated that elimination of dalbavancin occurs by both renal and non-renal routes (Leighton et al 2004;Cavaleri et al 2005). This is in contrast to vancomycin and teicoplanin which are eliminated primarily by the kidney.…”
Section: Pharmacokineticsmentioning
confidence: 90%
See 4 more Smart Citations
“…Investigators have demonstrated that elimination of dalbavancin occurs by both renal and non-renal routes (Leighton et al 2004;Cavaleri et al 2005). This is in contrast to vancomycin and teicoplanin which are eliminated primarily by the kidney.…”
Section: Pharmacokineticsmentioning
confidence: 90%
“…This is in contrast to vancomycin and teicoplanin which are eliminated primarily by the kidney. In a Phase I trial, urine excretion of unaltered drug accounted for only 33.5% of the elimination of a single dose of dalbavancin which was similar to the 34.5% noted in an animal model (Leighton et al 2004;Cavaleri et al 2005). Additionally, mild renal impairment (creatinine clearance of 50 to 80 ml/min) does not appear to alter dalbavancin's pharmacokinetic parameters (Dowell et al 2003).…”
Section: Pharmacokineticsmentioning
confidence: 91%
See 3 more Smart Citations